3-Hydroxypropionaldehyde (3-HPA) quantification by HPLC using a synthetic acrolein-free 3-hydroxypropionaldehyde system as analytical standard. Issue 112 (28th October 2015) - Burgé, G.; Flourat, A. L.; Pollet, B.; Spinnler, H. E.; Allais, F.
Abstract : HPLC-based quantification of 3-HPA using a synthetic acrolein-free 3-HPA standard obtained from commercially available 1, 2, 4-butanetriol through a straightforward and easy synthetic process. Abstract : HPLC-based quantification of 3-HPA using a synthetic acrolein-free 3-HPA standard obtained from commercially available 1, 2, 4-butanetriol through a straightforward and easy synthetic process has advantages over previous colorimetric methods of easier and safer implementation, and greater specificity. This HPLC method is very simple to implement in a lab, does not need any extra handling of the sample to be analyzed, and is suitable even in the presence of other aldehydes and 3-HPA derivatives, provided that the latter do not have similar retention times.